THEOREM OF BOREL TYPE FOR WHOLE ROWS DIRIHLE WITH ARBITRARY COMPLEX SEQUENCE OF INDEXES - Овчар, Ігор Євгенійович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In this article a Borel’s type relation |F(z)|(1+o(1)) μ (z,F), where z→∞ (z) between logarithms of maximum of the modulus of its sum and a maximal term of entire Dirichlet series with arbitrary sequence of complex exponents λ_n is obtained.